Pendampingan Motivasi Belajar Siswa melalui Penggunaan Ice Breaking dan Media Visual di MI Islamiyah Bumijaya - Hermanto, Hermanto; Hidayah, Sri; Hasanah, Uswatun (Jurnal Penelitian dan Pengabdian Masyarakat, 2023)
The aim of community service activities is to provide learning motivation through the use of Ice Breaking and Visual Media at MI Islamiyah Bumijaya. The implementation of PKM activities is carried out in several activity stages, including Problem Identification, Preparation of Program Plans, Training and Preparation, Program Implementation, Monitoring and Evaluation and Preparation of Final Reports. The results of this PKM activity obtained good results, such as increased motivation, student activity in class, and increased student learning concentration both in class and outside of class. The active involvement of teachers, students and parents has contributed to the success of this PKM program. This shows that investment in education has a positive impact on students' development and creates a brighter future for them